Research on the mechanism of Astragaloside Ⅳ in regulating urotensin Ⅱ-induced renal tubular epithelial cells injury through the RhoA/ROCK1 signaling pathway - Liu Qian-wei; Liu Wen-yuan; Fang Jing-ai (Linchuang shenzangbing zazhi)
ObjectiveTo explore the mechanism by which astragaloside IV （AS-IV） regulates the injury of normal rat kidney cells-52E （NRK-52E） induced by Urotensin II （UII） through the Ras homolog gene family member A （RhoA）/Rho-associated protein kinase 1 （ROCK1） signaling pathway.MethodsNRK-52E cells were cultured in vitro， and the effects of different concentrations of UII on NRK-52E cells were detected using the CCK8 assay. An appropriate concentration was selected for subsequent experiments. The experimental groups were divided as follows： （1）control group； （2）model group； （3）UII receptor antagonist group； （4）AS-IV group； （5）RhoA kinase inhibitor （fasudil） group； （6）losartan group. The expression levels of G protein-coupled receptor 14， α-smooth muscle actin （α-SMA）， and kidney injury molecule-1 （KIM-1） in each group of cells were detected using cell immunofluorescence. The mRNA expression levels of RhoA， ROCK1， and α-SMA in each group of cells were measured using reverse transcription polymerase chain reaction（RT-PCR）. The protein expression levels of RhoA， ROCK1， and caspase-1 in each group of cells were detected using Western blot.Results（1）The cell viability of the 0 mol/L UII group was 100%， while that in NRK-52E cells induced with 10-¹⁰， 10-⁹， 10-⁸， 10-⁷， and 10-⁶ mol/L UII was （51.52 ± 0.15）%， （61.70 ± 0.09）%， （71.90 ± 0.17）%， （61.27 ± 0.11）%， and （52.73 ± 0.13）%， respectively. UII could cause certain damage to cells， with the 10-⁸ mol/L UII group exhibiting less damage compared to the other four groups （P<0.05）. （2）Immunofluorescence results showed that the quantitative analysis of α-SMA immunofluorescence intensity in the control group， model group， SB-611812 group， AS-IV group， Fasudil group， and Losartan group was （6.72 ± 0.10）， （9.59 ± 2.23）， （8.00 ± 0.13）， （7.93 ± 0.14）， （8.09 ± 0.09）， and （8.10 ± 0.17）， respectively. The quantitative analysis of KIM-1 immunofluorescence intensity was （7.48 ± 0.09）， （10.42 ± 0.08）， （7.51 ± 0.08）， （7.71 ± 0.08）， （7.70 ± 0.07）， and （7.45 ± 0.15）， respectively. The quantitative analysis of GPR-14 immunofluorescence intensity was （4.05 ± 0.07）， （8.00 ± 0.06）， （5.04 ± 0.02）， （6.03 ± 0.07）， （6.02 ± 0.08）， and （6.02 ± 0.09）， respectively. （3）RT-PCR results showed that the quantitative analysis of α-SMA mRNA in the control group， model group， SB-611812 group， AS-IV group， Fasudil group， and Losartan group was （1.00 ± 0.00）， （1.96 ± 0.01）， （1.53 ± 0.02）， （1.52 ± 0.08）， （1.53 ± 0.03）， and （1.52 ± 0.09）， respectively. The quantitative analysis of mRNA level of RhoA was （1.00 ± 0.00）， （2.10 ± 0.02）， （1.44 ± 0.02）， （1.55 ± 0.03）， （1.53 ± 0.07）， and （1.66 ± 0.04）， respectively. The quantitative analysis of mRNA level of ROCK1 was （1.00 ± 0.00）， （2.09 ± 0.04）， （1.51 ± 0.02）， （1.56 ± 0.02）， （1.54 ± 0.01）， and （1.51 ± 0.02）， respectively. （4）Western Blot results showed that the quantitative analysis of protein expression of Caspase-1 in the control group， model group， SB-611812 group， AS-IV group， Fasudil group， and Losartan group was （1.00 ± 0.00）， （2.53 ± 0.03）， （1.57 ± 0.01）， （1.55 ± 0.09）， （1.56 ± 0.06）， and （1.56 ± 0.01）， respectively. The quantitative analysis of protein expression of RhoA was （1.00 ± 0.00）， （2.85 ± 0.08）， （1.62 ± 0.07）， （1.60 ± 0.01）， （1.61 ± 0.02）， and （1.60 ± 0.01）， respectively. The quantitative analysis of protein expression of ROCK1 was （1.00 ± 0.00）， （2.37 ± 0.09）， （1.45 ± 0.05）， （1.54 ± 0.03）， （1.39 ± 0.05）， and （1.52 ± 0.01）， respectively.ConclusionAS-Ⅳ alleviates UⅡ-induced NRK-52E cell damage by downregulating the RhoA/ROCK1 signaling pathway.